Tethering role of the autonomic nervous system on cardioventilatory coupling - Colombo, Riccardo; Wu, Maddalena Alessandra; Perotti, Andrea; Saia, Laura; Fossali, Tommaso; Ottolina, Davide; Borghi, Beatrice; Castelli, Antonio; Rech, Roberto; Cogliati, Chiara; Catena, Emanuele (Respiratory physiology & neurobiology, 2020)
•Positive pressure ventilation with changes of volemia affect the autonomic control of hemodynamics and the preload of left cardiac chambers.•Correction of hypovolemia increases the vagal outflow leaving unchanged the sympathetic modulation and enhances the baroreflex sensitivity.•Cardioventilatory coupling is affected by both volemia and ventilatory mode mainly in the respiratory driven frequencies. Hypovolemia and intermittent positive pressure ventilation are conditions that frequently characterize the state of critical illness, but their interaction and resulting cardioventilatory coupling is poorly understood even in healthy humans. We explored heart rate variability, baroreflex activity, and their interaction in an experimental protocol involving twelve mildly hypovolemic healthy subjects during spontaneous breathing and noninvasive positive-pressure ventilation. In seven subjects, an echocardiographic assessment was also performed. Correction of hypovolemia, raising cardiac preload, produced an increase in high-frequency spectral power density of heart rate, left low-frequency spectral power density unchanged but enhanced baroreflex sensitivity. Cardioventilatory coupling was affected by both central blood volume and ventilatory mode and was mainly entrained by the respiratory oscillation. In conclusion, the autonomic nervous system and baroreflex have a significant role in compensating the hemodynamic perturbation due to changes of volemia and ventilatory-induced fluctuations of venous return. They exert an integrative function on the adaptive pattern of cardioventilatory coupling.